Chad : Request for a Three-Year Arrangement Under the Extended Credit Facility. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2014)
KEY ISSUES Context: Chad is a fragile country with weak institutional capacity that needs to manage volatile and exhaustible oil revenues prudently to tackle its large development needs. Chad is enjoying a period of domestic political stability, but major regional security issues are imposing significant fiscal costs in both the short and medium term. Macroeconomic policy over the last few years has achieved a gradual tightening of the underlying fiscal policy stance together with a sizable increase in public investment. Satisfactory performance under an SMP in 2013 demonstrated the authorities' commitment to improved macroeconomic management and has set the ground for an upper credit tranche arrangement with the Fund. Policy Framework: The government's medium-term economic program, anchored by the 2013-2015 National Development Plan (NDP), aims at reinforcing economic growth and making it more inclusive, while maintaining macroeconomic stability and fiscal sustainability. Given the continued heavy dependence on volatile oil revenues that are projected to decline over the long-term and the currently high risk of debt distress, macroeconomic policies target a sustained fiscal adjustment, a buildup of liquidity buffers, and economic diversification. Those objectives will be underpinned by a reform agenda focused on strengthening public financial and debt management and improving the business environment. Request for an Extended Credit Facility arrangement: In the attached letter of intent, the authorities request a three-year arrangement under the Extended Credit Facility (ECF) in the amount of SDR 79.92 million (120 percent of quota) in support of their medium-term economic program. The ECF arrangement is expected to address the country's protracted balance of payments' problems resulting from a trend reduction in oil revenues, maintain adequate international reserves' coverage, and play a catalytic role for bilateral and multilateral assistance to Chad. The accompanying memorandum of economic and financial policies spells out in more detail the objectives of the program and policy actions that the government of Chad envisages to undertake during 2014-17.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet